METODE PEMBELAJARAN PENDIDIKAN ISLAM PADA PENYANDANG DISABILITAS - Zakaria, Zakaria (STAI Darul Qalam Tangerang, 2021)
Persons with disabilities are people who have physical or mental limitations, can also be called a person with a disability. Physical disability is a disability that results in disruption to bodily functions, including bodily movements, vision, hearing, and the ability to speak. Mental disability is a mental disorder and behavior of both congenital defects and as a result of illness. Islamic Religious Education for children with disabilities aims to develop the potential that is still owned optimally, so they can live independently and be able to adjust to the environment in which they are. This journal is intended to answer the problem of: 1) How is the Method of Learning Islamic Religious Education for persons with disabilities in SKh Negri 01 Pandeglang and SKh Negri 01 Serang City 2) How is the Use of Islamic Religious Education Learning Media in the two Special Schools? 3) How is the Implementation of Islamic Education Learning Evaluation in the Two Special Schools? 4) What are the Supporting and Inhibiting Factors found in the Learning of Islamic Religious Education? This journal research method uses qualitative research. The data collection techniques adopted consisted of, firstly through searching and reviewing various literature related to Islamic Education Learning Methods in Negh 01 Government Guidance in Pandeglang and Negh 01 Government Serang. Second through field research: interviews, observations and documentation of SKh Negri 01 Coaching Pandeglang and SKh Negri 01 Serang City Based on the research conducted, it was concluded that the Islamic Religious Education Learning Method in SKh Negri 01 Guidance on Pandeglang and SKh Negri 01 Serang City varied - all of which aimed to achieve satisfying learning outcomes, as well as learning media and the evaluation of the learners were truly selected and adjusted to the situation of students